Mammal Taphonomy in a Cave Deposit From Quaternary of Brazil - Trifilio, Lucas Henrique Medeiros da Silva; Araújo-Júnior, Hermínio Ismael de; Porpino, Kleberson de Oliveira; Barbosa, Fernando Henrique de Souza (Frontiers in Ecology and Evolution, 2022)
In Brazil, the Quaternary caves of the Brazilian Intertropical Region (BIR) host important fossiliferous deposits of terrestrial vertebrates, whose fossil content is taxonomically well known. Here, we conducted a taphonomic analysis based on macroscopic and microscopic features of 543 specimens collected in the F3 cave, a fossiliferous deposit located in the municipality of Felipe Guerra, northeast of Brazil. This deposit encompasses 17 taxa, but it is dominated by fossils of Eremotherium laurillardi. Most bones were buried in less than a year, but the taphonomic history of this deposit was governed by alternation of dry and wet cycles. This led us to recognize four taphonomic modes, that differ according to the climatic conditions in which the bones were preserved as well as the time interval between the accumulation and the final burial of the remains.